Applied Phonetics in Oral Reading - Mendoza, Aida (2004)
Suprasegmental description in Spanish which includes rules forsegmentation, stress assignment, syllabicaton, phonic cohesion andrhythm in general, is used in this article to offer sorne hints for readingaloud texts in verse and prose. Those interested in oral interpretation ofwritten material for audiences are here introduced to a series of exercisesdesigned to ensure fluency.